Sustainable Paper Production Using Treated Pineapple Leaf Fiber and Wastepaper Composites - Nur Syabila Husna Mohd Bakti; Liew Cheng Yeu; Wong Qi Hui; Adibah Rahmat; Nur Farhana Mohd Hashim; Tuan Sharatul Adawiah Tuan Zakri; Pauzan, Mohammad Arif Budiman; Zalilah Murni Mat Ali @ Yunus; Saliza Asman (Journal of Science and Technology, 2025)
Fibers extracted from plants offer alternatives to commercial materials to produce paper which are increasingly valuable in sustainable product development. This study investigates the potential of pineapple leaf fibers (PALF) as an alternative to synthetic fibers in composite with wastepaper for recycle paper fabrication to reduce the agricultural waste. The study focuses on the extraction and characterization by emphasizing the effects of alkaline treatment using sodium hydroxide (NaOH) on the physical and mechanical properties of the PALF. Wastepaper was then combined with treated PALF in varying ratios i.e. 1:1, 1:2, and 2:1 to create the composite paper. The properties of the synthesized PALF were evaluated in term of moisture content and tensile strength. While the morphological characteristics was evaluated using Scanning Electron Microscopy (SEM) and functional group determination by Fourier Transform Infrared Spectroscopy (FTIR). Results indicate that NaOH treatment significantly enhances the mechanical properties of PALF by improving fiber strength and reducing moisture content with the 1:2 ratio demonstrating the highest tensile strength (9234.596 Pa). Compared to the 1:1 ratio which exhibited a tensile strength of 6946.375 Pa, the 1:2 ratio resulted in a 32.9% increase in tensile strength. Similarly, when compared to the 2:1 ratio (5311.917 Pa), the 1:2 ratio showed an impressive 73.9% enhancement in tensile strength. These findings suggest that increasing the proportion of wastepaper relative to pineapple leaf fiber (PALF) enhances fiber bonding and mechanical strength, likely due to better fiber interlocking and reinforcement. With its high tensile strength and improved durability, this composite paper can be utilized in packaging materials, stationery and biodegradable wrapping papers. This study highlights the viability of PALF in the development of eco-friendly composite materials, contributing to waste reduction and promoting the use of renewable resources in material science.